2019
DOI: 10.1093/jmcb/mjz107
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of PLK1 by SET7/9 ensures accurate kinetochore–microtubule dynamics

Abstract: Abstract Faithful segregation of mitotic chromosomes requires bi-orientation of sister chromatids, which relies on the sensing of correct attachments between spindle microtubules and kinetochores. Although the mechanisms underlying PLK1 activation have been extensively studied, the regulatory mechanisms that couple PLK1 activity to accurate chromosome segregation are not well understood. In particular, PLK1 is implicated in stabilizing kinetochore–microtubule att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…To assess the impact of Apolo1 deficiency on PLK1 activity, we introduced two siRNA oligonucleotide duplexes to Apolo1 by transfection into HeLa cells and carried out western blotting analyses using phosphorylated PLK1 (pT210-PLK1) as the readout ( Liu et al, 2012 ; Yu et al, 2020 ). As shown in Figures S1C and S1D , western blotting with anti-Apolo1 antibody and quantitative analysis revealed that the two independent siRNA oligonucleotides caused remarkable suppression of Apolo1 protein levels at 48 h. This suppression was specific, because it did not alter the levels of other proteins, such as tubulin, PLK1, and Aurora B ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the impact of Apolo1 deficiency on PLK1 activity, we introduced two siRNA oligonucleotide duplexes to Apolo1 by transfection into HeLa cells and carried out western blotting analyses using phosphorylated PLK1 (pT210-PLK1) as the readout ( Liu et al, 2012 ; Yu et al, 2020 ). As shown in Figures S1C and S1D , western blotting with anti-Apolo1 antibody and quantitative analysis revealed that the two independent siRNA oligonucleotides caused remarkable suppression of Apolo1 protein levels at 48 h. This suppression was specific, because it did not alter the levels of other proteins, such as tubulin, PLK1, and Aurora B ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…In vertebrate cells, PLK1 localizes to kinetochores during early mitosis and usually accumulates on unaligned chromosomes ( Ahonen et al, 2005 ; Liu et al, 2012 ; Yu et al, 2020 ). During early mitosis, PLK1 stabilizes kMT attachments at kinetochores, whereas Aurora B destabilizes kMT attachments at kinetochores ( Godek et al, 2015 ; Lampson and Kapoor, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to TUBEs for ubiquitination analysis, methyl-binding domains have been exploited for enrichment purposes. The affinity of naturally occurring triple malignant tumor-binding domains (3×MBT) from the protein L3MBTL1, for mono- and di-methylated lysine residues of proteins resulted in the use of these domains for enrichment [ 173 , 174 ]. Recently, Wang et al [ 175 ] described a new chromatography-based method of methylome analysis combining SCX, IMAC and high-pH reversed-phase chromatography which led to the identification of 765 methylation sites [ 175 ].…”
Section: Analytical Techniques In Post-translational Modification Analysismentioning
confidence: 99%
“…Plk1 kinase activity is activated via phosphorylation of its T-loop on Thr210 by Aurora A kinase (Maců rek et al, 2008;Seki et al, 2008) and possibly by other kinases (Paschal, Maciejowski, & Jallepalli, 2012). Methylation on Lys191 of Plk1 by methyltransferases SET7/9 inhibits Plk1 kinase activity (Yu et al, 2020). This modification presumably allows for fine-tuning of Plk1 activity at the kinetochores, though a demethylase has not yet been identified.…”
Section: Early Mitotic Spindle Assembly-centromerementioning
confidence: 99%